Memorial playgrounds: Special ways of coping with extreme loss - Sandberg Birgitta; Hurmerinta Leila; Menzfeld Mira (Taylor & Francis (Commercial Publisher), 2022)
The purpose of this study was to understand how active coping with extreme loss takes place when creating memorial playgrounds, as well as in relation to existing memorial playgrounds. Using qualitative methods and drawing from 63 cases, the research enriches our understanding of bereavement by revealing the central mechanisms through which active coping takes place and by presenting the distinct elements that the mechanisms are composed of. The study contributes to the research on bereavement by showing how active coping takes place both as an outcome of and during the memorial creation process.